(untitled) (International journal of artificial intelligence, 2026)
This article examines how digital transformation can improve the competitiveness of industrial enterprises. Recent official and academic sources show that digital transformation strengthens industrial performance not only through automation, but also through productivity growth, innovation, business-model adaptation, supply-chain coordination, and resilience. OECD materials describe the current period as one of rapid technological change, while UNIDO links digitalization with industrial development and future industrial competitiveness. Recent empirical studies likewise show that digital transformation can significantly improve manufacturing competitiveness, firm productivity, industrial-chain resilience, and green innovation.